REMOTE DIAGNOSIS OF TRAUMATIC PROSTHETIC STOMATITIS USING A TELEMEDICINE DEVICE - Sukalenko, Vitalii; Tsyhanok, Oleksandr (Eastern Ukrainian Medical Journal, 2024)
The digital photography protocol has been successfully applied in various areas of dental practice. The use of digital photography in teledentistry expands the possibilities for the remote diagnosis of a range of dental conditions. Several authors described the use of digital photography for diagnosing diseases of the oral mucosa and remote assessment of traumatic dental injuries.The aim of this study was to assess the level of agreement between experts when suspecting traumatic prosthetic stomatitis caused by partial removable dentures (PRDs) by comparing in-person and remote diagnoses.Materials and methods: This study included 57 patients who were fitted with PRDs. Patients received treatment at the clinic of the dentistry department of the Educational-Scientific Medical Institute of Sumy State University (Sumy) and the dental office of the University Clinic of Sumy State University (Sumy). Clinical examination data were recorded in the outpatient dental record (form 043/o), and digital photographs were taken using a telemedicine device camera, stored on the device's memory card, and synchronized with cloud storage. Six experts remotely formulated their diagnoses based on an analysis of digital photographs. The accuracy of remote diagnosis was assessed by comparing it to the "gold standard" of in-person diagnosis at the clinic. Data were analyzed using Gwet's AC1 test to evaluate the agreement between the two methods.Results: The agreement levels between researchers for in-person and remote diagnoses formulated exclusively using images were 0.83 or higher (95% confidence interval: 0.73–0.91).Conclusion: The accuracy of remote diagnoses was comparable to those made directly in the clinic. Telemedicine systems can be an effective tool for the remote visual assessment of a patient's condition during the post-prosthesis period. Keywords: Teledentistry, prosthetic stomatitis, partial removable dentures, diagnostic visualization.